Quantitative ethnobotany of medicinal plants used by indigenous communities of Gandhamardan Mountain Chains at Bargarh District of Odisha, India - Pandey, Abhishek Kumar; Pradhan, Subham; Bux, Faiz (Ethnobotany Research and Applications, 2024)
Background: This study aims to collect the traditional medicinal knowledge among the tribal communities and residents of villages near the Gandhamardan Mountain Chain in the Bargarh District of Odisha, India. Method: From Dec 2022 to May 2023, ethnobotanical surveys were done using interviews, discussions, and observations. Data from 85 participants included plant names, uses, preparation, and administration methods. The quantitative analysis involved RFC, UV, and ICF. Participants comprised 62 males and 23 females, contributing to diverse knowledge from various communities. Results: In this area, 70 plants from 65 genera and 36 families are employed for medicinal purposes. The primary families used are Fabaceae, followed by Asteraceae. Leaves are the preferred plant part for medicinal preparations. The most favoured method to extract medicinal properties is obtaining plant juice, succeeded by decoction. The top RFC values are attributed to Tridax procumbens (0.54), Ocimum sanctum (0.51), Boerhavia diffusa (0.38), and Cynodon dactylon (0.38). For UV, the leading values are for Tridax procumbens (0.67), Ocimum sanctum (0.61), and Cynodon dactylon (0.54). The highest ICF value pertains to neurological and psychological disorders (1.00), followed by fever, cold, and cough (0.95), and musculoskeletal disorders (0.92), with the lowest in hormonal disorders (0.58). Conclusion: Maiden ethnobotanical study in this area unveiled novel ethnomedicinal plant uses. Traditional healers and elders participated, offering vital documentation for future drug discovery and research. Keywords: Traditional medicine, ethnobotanical knowledge, Indigenous uses, RFC, UV, ICF